Apolipoprotein-B and LDL-cholesterol levels in a young group of maracaibo - Bonezzi S, Eleonora; Casanova R, Ilya; Gomez G, María; Casanova, Angel; Villalobos, Ana Ortega (Medicina (Ribeirao Preto), 2002)
The purpose of this study was determine if the apolipoprotein-B concentrations (g/L) are correlated with the LDL-Cholesterol (mg/dL), and at the same time, to inquest the possibility to apply them to the population of Maracaibo, in substitution of the Friedewald formula for LDL-Cholesterol. The apolipoprotein-B serum concentrations were studied in a sample of 41 subjects (27 females and 14 males) between 20 and 39 years of age, users of the Bioanalisis School’s Clinical Laboratory, Zulia University in Maracaibo. Measurements of glycaemia, Total Cholesterol, Triglycerides and LDL-Cholesterol were made. The Apolipoprotein-B was determined by Inmunoturbidimetric method. The apolipoprotein-B levels were 0.93 ± 0.3 g/L in the female group and 1.06 ± 0.31 g/L in the male group. The correlation between apolipoprotein-B and LDLCholesterol was 0.8640. Linear regression analysis was applied, and formulas were obtained to calculate LDL-Cholesterol from apolipoprotein-B concentrations, representing a statistical formula that should be corroborated experimentally. The risk level of apolipoprotein-B ( ³ 1.2 g/L) was set in the percentiles 95 th for females and 75 th for males.